2019
DOI: 10.1111/mec.15223
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale biogeography and environmental regulation of methanotrophic bacteria across boreal inland waters

Abstract: Aerobic methanotrophic bacteria (methanotrophs) use methane as a source of carbon and energy, thereby mitigating net methane emissions from natural sources. Methanotrophs represent a widespread and phylogenetically complex guild, yet the biogeography of this functional group and the factors that explain the taxonomic structure of the methanotrophic assemblage are still poorly understood. Here, we used high‐throughput sequencing of the 16S rRNA gene of the bacterial community to study the methanotrophic communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 113 publications
6
25
0
Order By: Relevance
“…As Lake Simoncouche is shallow and well oxygenated, anaerobic metabolism is likely limited compared to aerobic metabolism. Moreover, Crevecoeur et al (2019) recently showed that methanotrophs on the surface waters only constitute for about 0.1% of the bacterial community in Quebec lakes. Because of the depleted 13 C values of methane (about À70&), zooplankton biomass found with methane contribution in a boreal lake has consequently very depleted 13 C values (about À50&; Kankaala et al 2006).…”
Section: Stable Isotope Analyses and Allochthonymentioning
confidence: 99%
“…As Lake Simoncouche is shallow and well oxygenated, anaerobic metabolism is likely limited compared to aerobic metabolism. Moreover, Crevecoeur et al (2019) recently showed that methanotrophs on the surface waters only constitute for about 0.1% of the bacterial community in Quebec lakes. Because of the depleted 13 C values of methane (about À70&), zooplankton biomass found with methane contribution in a boreal lake has consequently very depleted 13 C values (about À50&; Kankaala et al 2006).…”
Section: Stable Isotope Analyses and Allochthonymentioning
confidence: 99%
“…However, the impact of those environmental parameters on the methanotrophic communities is still unclear and often seems contradictory (Ho et al, 2013). Furthermore, most studies on freshwater MO neglect the potential importance of anaerobic MO and Verrucomicrobia as they are less abundant (Ho et al, 2013;Knief, 2015;Crevecoeur et al, 2017Crevecoeur et al, , 2019Reis et al, 2020). As the role of rare microorganisms is still poorly understood (Galand et al, 2009), there is a pressing need to include those into the analyses for a complete understanding of the functioning and interactions in the methanotrophic community.…”
Section: Introductionmentioning
confidence: 99%
“…Rare taxa can also serve as a seed for when conditions change (Graf et al, 2018;Mayr et al, 2020b) and should therefore be considered. Also, methodological issues should be taken into account as most previous studies on methanotrophs have been done using PCR-based methods looking into the diversity of 16S rRNA or pmoA genes (Crevecoeur et al, 2017(Crevecoeur et al, , 2019Rissanen et al, 2018;Mayr et al, 2020c). While being a well-established method in microbial ecology, it introduces biases to the data, especially in primer mismatches and problems related to coverage of especially new and poorly known taxa (Bourne et al, 2001;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic MOX, often inhabiting anoxic–oxic interfaces such as the upper sediment layers, are known to support a high potential for CH 4 oxidation in riverbeds (Trimmer et al., 2015). Furthermore, a large‐scale study on methanotrophic communities in boreal inland waters in Canada highlighted a clear niche differentiation between type I and type II methanotrophs in water and river sediments (Crevecoeur et al., 2019). Besides these works on specific groups, however, the taxonomic composition/distribution of both, methanogens and methanotrophs and the respective predominant key players in different streams across ecoregions have not yet been examined.…”
Section: Introductionmentioning
confidence: 99%